Peranan Kejaksaan dalam Penanganan Perkara Pelecehan Seksual Anak Dibawah Umur Di Kabupaten Aceh Barat - Desi Maulida; Nila Trisna (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2022)
This research is entitled "The role of the prosecutor in handling cases of sexual abuse of minors in Aceh Regency. The method used is empirical and the data analysis used is qualitative, the data collection technique is conducted interviews and documentation, the type of data used is primary data, secondary data, based on the results of research on proving that in Aceh Province, especially in West Aceh, there are cases of child abuse under This age and the indictment dropped by the public pros ecutor are in accordance with the Aceh Qanun law, in the process of handling cases of sexual abuse of minors, the application or working method of the public prosecutor is in accordance with the prosecutor's law, although there are tips and certain tricks contained in the m legislation used by the prosecutor's office.